Development of E-Modules with SSCS Model to Improve Students’ Critical Thinking Skills on Energy Crisis Materials - Farah Dhilah Balqis; Yayuk Mulyati; Arista, Rini Anggi; Nugraheni, Dian; Setiawan, Agung Mulyo (Indonesian Journal of Biology Education, 2025)
This research aims to develop and validate an e-module based on the Search, Solve, Create, and Share (SSCS) learning model to facilitate students' critical thinking skills on energy crisis materials. The research uses the ADDIE development model, which is limited to the formative evaluation stage, including needs analysis, design, development, and readability and practicality tests. The results of expert validation show that the e-module is in the "quite valid" category with an average of 83.2%. The readability test obtained results of 89.25% from students and 88.4% from teachers (outstanding category), while the practicality test by teachers reached 91.67% (convenient category). The results of the Fleiss’ Kappa test showed a “moderate” level of agreement on the SSCS syntax (0.50) and the critical thinking indicator (0.57). The e-module also features interactive features such as learning videos and contextual educational games. These findings indicate that SSCS-based e-modules are suitable for use as science learning media to encourage the strengthening of students’ critical thinking skills independently and contextually. The implications of this research suggest that integrating the SSCS model into digital learning media can enhance students’ engagement and reflective thinking, and it provides a foundation for future experimental studies to measure its effectiveness in improving learning outcomes.